Development of Microsatellite Markers Based on Transcriptome Sequencing and Evaluation of Genetic Diversity in Swimming Crab (Portunus trituberculatus) - Duan, Baohua; Mu, Shumei; Guan, Yueqiang; Liu, Weibiao; Kang, Tongxu; Cheng, Yana; Li, Zejian; Tian, Yang; Kang, Xianjiang (Frontiers in Genetics, 2022)
Portunus trituberculatus is an economically important mariculture species in China. Evaluating its genetic diversity and population structure can contribute to the exploration of germplasm resources and promote sustainable aquaculture production. In this study, a total of 246,243 SSRs were generated by transcriptome sequencing of P. trituberculatus. Among the examined 254,746 unigenes, 66,331 had more than one SSR. Among the different SSR motif types, dinucleotide repeats (110,758, 44.98%) were the most abundant. In 173 different base repeats, A/T (96.86%), AC/GT (51.46%), and ACC/GGT (26.20%) were dominant in mono-, di-, and trinucleotide, respectively. GO annotations showed 87,079 unigenes in 57 GO terms. Cellular process, cell, and binding were the most abundant terms in biological process, cellular component, and molecular function categories separately. A total of 34,406 annotated unigenes were classiﬁed into 26 functional categories according to the functional annotation analysis of KOG, of which “general function prediction only” was the biggest category (6,028 unigenes, 17.52%). KEGG pathway annotations revealed the clustering of 34,715 unigenes into 32 different pathways. Nineteen SSRs were identified as polymorphic, and thus used to assess the genetic diversity and structure of 240 P. trituberculatus individuals from four populations in the Bohai Sea. Genetic parameters analysis showed a similar level of genetic diversity within wild populations, and the cultured population indicated a reduction in genetic diversity compared with wild populations. The pairwise FST values were between 0.001 and 0.04 with an average of 0.0205 (P < 0.05), suggesting low but significant level of genetic differentiation among the four populations. Structure analysis demonstrated that the four populations were classiﬁed into two groups including cultured group and other populations. The phylogenetic tree and PCA revealed that vast number of samples were clustered together, and that cultivated individuals were distributed more centrally than wild individuals. The findings contribute to the further assessment of germplasm resources and assist to provide valuable SSRs for marker-assisted breeding of P. trituberculatus in the future.